Strategies and bottlenecks to tackle infodemic in public health: a scoping review - Gentili, Andrea; Villani, Leonardo; Osti, Tommaso; Corona, Valerio Flavio; Gris, Angelica Val; Zaino, Andrea; Bonacquisti, Michele; De Maio, Lucia; Solimene, Vincenzo; Gualano, Maria Rosaria; Favaretti, Carlo; Ricciardi, Walter; et al. (Frontiers in Public Health, 2024)
Background The World Health Organization defines “infodemic” as the phenomenon of an uncontrolled spread of information in digital and physical environments during a disease outbreak, causing confusion and risk-taking behaviors that can harm health. The aim of this scoping review is to examine international evidence and identify strategies and bottlenecks to tackle health-related fake news. Methods We performed a scoping review of the literature from 1 January 2018 to 26 January 2023 on PubMed, Web of Science, and Scopus electronic databases. We also performed a search of grey literature on institutional websites. The research question has been defined according to the PCC (population, concept, and context) mnemonic for constructing research questions in scoping reviews. Results The overall research in the scientific databases yielded a total of 5,516 records. After removing duplicates, and screening the titles, abstracts, and full texts, we included 21 articles from scientific literature. Moreover, 5 documents were retrieved from institutional websites. Based on their content, we decided to group recommendations and bottlenecks into five different and well-defined areas of intervention, which we called strategies: “foster proper communication through the collaboration between science and social media companies and users,” “institutional and regulatory interventions,” “check and debunking,” “increase health literacy,” and “surveillance and monitoring through new digital tools.” Conclusion The multidisciplinary creation of standardized toolkits that collect recommendations from the literature and institutions can provide a valid solution to limit the infodemic, increasing the health education of both citizens and health professionals, providing the knowledge to recognize fake news, as well as supporting the creation and validation of AI tools aimed at prebunking and debunking.